Tropical laboratory research to support sustainability issues: A systematic literature review - H. Husamah; Abdulkadir Rahardjanto; Ahmad Adnan Mohd Shukri (Universitas Muhammadiyah Malang, 2024)
Background: The study of tropical laboratory research to support sustainability issues is very urgent to ensure that efforts to conserve and utilize natural resources in tropical areas can be carried out effectively and sustainably. Objectives: This SLR focuses on analyzing research trends in relation to “tropical laboratory research to support sustainability issues”. Methods: This SLR will provide a relatively complete analysis so that it can inspire research activities for researchers, especially in countries that do not yet have a high interest in this aspect. This investigation constitutes a SLR to systematically identify, assess, and analyze all specific research inquiries, topics, or areas. The sequence of inclusion and exclusion was using PRISMA. Data simulation uses